2015
DOI: 10.1097/bot.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

What Makes an Intertrochanteric Fracture Unstable in 2015? Does the Lateral Wall Play a Role in the Decision Matrix?

Abstract: Intertrochanteric (IT) fractures pose a tremendous burden to the healthcare system. Although consistently good results are obtained while treating stable IT fractures, treatment failure rates with unstable fractures are much higher, and hence, it is imperative to identify unstable patterns. Presently, the conventionally classified unstable configurations (fracture with posteromedial comminution, reverse oblique, IT with subtrochanteric extension) and the recently added fracture patterns (IT fractures with avul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 20 publications
0
47
0
1
Order By: Relevance
“…Multiple clinical trials and meta-analyses have directly compared the two techniques for treatment of these fractures [3, 18-20, 27, 28, 30, 34]. Particular fracture patterns, such as those with reverse obliquity, subtrochanteric extension, fracture extension into the lateral wall, or greater trochanteric avulsion [23,26,33], have lower rates of failure and reoperation when treated with a cephalomedullary nail than a sliding hip screw. However, to our knowledge, no study has found one construct to be clearly superior in the treatment of commonly encountered conventional obliquity fracture patterns, and controversy over the optimal treatment strategy persists [3,5,25,27,28,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical trials and meta-analyses have directly compared the two techniques for treatment of these fractures [3, 18-20, 27, 28, 30, 34]. Particular fracture patterns, such as those with reverse obliquity, subtrochanteric extension, fracture extension into the lateral wall, or greater trochanteric avulsion [23,26,33], have lower rates of failure and reoperation when treated with a cephalomedullary nail than a sliding hip screw. However, to our knowledge, no study has found one construct to be clearly superior in the treatment of commonly encountered conventional obliquity fracture patterns, and controversy over the optimal treatment strategy persists [3,5,25,27,28,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Type I is defined as a type of intertrochanteric fracture but the pathology is similar to that of pertrochanteric fractures associated with a lateral wall fracture. Since bony factors supporting the proximal bone fragment are lost, this type may induce rotation instability and/or excessive telescoping [2]. Therefore, either SHS with a trochanteric buttress support should be used to stabilize the proximal primary fragment or SFN which also acts as "a lateral prosthetic wall" [2] may be used.…”
Section: Discussionmentioning
confidence: 99%
“…Since bony factors supporting the proximal bone fragment are lost, this type may induce rotation instability and/or excessive telescoping [2]. Therefore, either SHS with a trochanteric buttress support should be used to stabilize the proximal primary fragment or SFN which also acts as "a lateral prosthetic wall" [2] may be used. Type I sometimes looks like Reverse Oblique Pattern (Type III) depending on the course of the LFL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations